Caving subsidence backfilling: case studies - Jakubec, J.; Xu, Y.-H.; Thomas, A. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Cave mining methods, including block, panel, and sublevel caving, invariably result in surface subsidence as the extraction of material at depth triggers upward propagation of the cave. This process typically begins with undetectable elastic deformation before progressing to visible surface fracturing and the eventual formation of a subsidence crater. As mining continues, these craters expand both laterally and vertically, with unsupported walls subjected to chronic sloughing and erosion. To mitigate the extensive surface footprint, reduce environmental liabilities, and potentially lower closure costs, backfilling the subsidence zone of influence with waste rock or conditioned tailings is increasingly being considered and studied as a proactive engineering solution. This paper examines the technical and economic considerations of backfilling strategies and draw on several global case studies. The findings suggest that while backfilling could effectively limit lateral expansion, reduce water inflow or provide alternative waste rock or tailings storage, success depends on rigorous hydrological management and a detailed understanding of site-specific geotechnical responses.